Craving mediates the effect of impulsivity on lapse-risk during alcohol use disorder treatment. (June 2020) - Coates, Jason M.; Gullo, Matthew J.; Feeney, Gerald F.X.; McD. Young, Ross; Dingle, Genevieve A.; Clark, Paul J.; Connor, Jason P.
Highlights: Rash impulsiveness predicted more frequent alcohol craving. Craving was associated with greater risk of lapse during treatment. Craving mediated rash impulsiveness in the prediction of lapse. Relative risk of lapse associated with craving increased as treatment progressed. Rash impulsiveness did not increase risk of lapse in response to craving. Abstract: Rash impulsiveness, the propensity for approach behaviour despite potential negative consequences, is associated with stronger alcohol craving in patients with Alcohol Use Disorder (AUD). This relationship is poorly understood and implications for treatment response are unexamined. This study explored the relationship between rash impulsiveness, craving, and treatment response among 304 outpatients enrolled in a 12-week abstinence-based Cognitive-Behavioural Therapy (CBT) program for AUD. Assessments were completed pre-and-post treatment, with craving and alcohol consumption monitored at each treatment session. Higher rash impulsiveness predicted more frequent craving over treatment ( b = 0.95, 95% CI = 0.40, 1.50). Higher craving was associated with greater lapse-risk ( b = 0.04, 95% CI = 0.03, 0.05), with the association between craving and lapse-risk increasing as treatment progressed ( b = 0.01, 95% CI = 0.01, 0.02). Craving positively mediated the relationship between rash impulsiveness and lapse-risk (µ = 0.38, 95% CI = 0.10, 0.70). Contrary to hypotheses, the risk of lapse in response to craving was not moderated by rash-impulsiveness. These results suggest that AUD patients with a predisposition for rash impulsiveness are more vulnerable to alcohol craving, and subsequently, poorer treatment outcomes.